The Still Underestimated Problem of Fungal Diseases Worldwide - Almeida, Fausto; Rodrigues, Marcio L.; Coelho, Carolina (Frontiers in Microbiology, 2019)
In the past few years, fungal diseases cause estimated over 1.6 million deaths annually and over 1 billion people suffer from severe fungal diseases. Public health surveillance of fungal diseases is generally not compulsory, suggesting that most estimates are conservative. Fungal disease can also damage plants and crops, causing major losses in agricultural activities and food production. Animal pathogenic fungi are threatening bats, amphibians and reptiles with extinction. It is estimated that fungi are the highest threat for animal-host and plant-host species, representing the major cause (approximately 65%) of pathogen-driven host loss. In this complex scenario, it is now clear that the global warming and accompanying climate changes have resulted in increased incidence of many fungal diseases. On the basis of all these factors, concerns on the occurrence of a pandemic of fungal origin in a near future have been raised. In this context, to stop forgetting and underestimating fungal diseases is mandatory.